2022
DOI: 10.1177/00207314221133063
|View full text |Cite
|
Sign up to set email alerts
|

Gender Variations and Inequity in Health Care Financing: Evidence from Southeast Nigeria

Abstract: Health care is central to sustainable development, but it is underfunded in many developing countries such as Nigeria. This study empirically examined gender variations and inequity in health care financing in Southeast Nigeria. To decompose the Gini coefficient and analyze inequity by gender and differences in health care financing among states in the region, Dagum's approach for decomposition of the Gini coefficient is used. Empirical results showed that gender inequity exists in health care financing in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This interesting outcome concurs with our expectations and Nadome's (2014) finding. Other previous Malaysian studies also found ethnic differences in consumer expenditure behaviour, but they focused solely on health expenditure among the general population (Ang & Cheah, 2023;Cheah et al, 2021). Why Malays spent less than Chinese is not clear because indepth interviews were not carried out, but culture or religion could be a plausible reason.…”
Section: Discussionmentioning
confidence: 90%
“…This interesting outcome concurs with our expectations and Nadome's (2014) finding. Other previous Malaysian studies also found ethnic differences in consumer expenditure behaviour, but they focused solely on health expenditure among the general population (Ang & Cheah, 2023;Cheah et al, 2021). Why Malays spent less than Chinese is not clear because indepth interviews were not carried out, but culture or religion could be a plausible reason.…”
Section: Discussionmentioning
confidence: 90%